Potential role of lava lizards as pollinators across the Galápagos Islands - Hervías-Parejo, Sandra (2020)
Lizards have been reported as important pollinators on several oceanic islands. Here we evaluate the potential role of Galápagos lava lizards (Microlophus spp.) as pollinators across their radiation. Over 3 years, we sampled pollen transport by 9 lava lizard species on the 10 islands where they are present, including 7 single-island endemics. Overall, only 25 of 296 individuals sampled (8.4%) transported pollen of 10 plant species, the most common being Prosopis juliflora, Exodeconus miersii, Sesuvium sp. and Cordia leucophlyctis. At least 8 of these plant species were native, and none were confirmed as introduced to the archipelago. Despite the low overall proportion of individuals carrying pollen, this was observed in 7 of the nine lizard species, and on 8 of the ten main islands (Española, Fernandina, Floreana, Isabela, Marchena, Pinta, Santa Cruz and Santiago), suggesting that this is a widespread interaction. The results reported here support the potential role of lava lizards as pollinators across their radiation, although they may represent a relatively modest contribution when compared with birds and insects. However, we cannot discard that lizards may be ecologically significant for particular plant species and ecosystems given the specific climatic condition and functional diversity of each island.